A comparative study of hyperbaric bupivacaine versus hyperbaric bupivacaine and fentanyl (12.5 mcg) in subarachnoid anesthesia for lower abdominal and lower extremity surgeries - Indurkar, Pradeep Samuel; Saibaba, Samala (International Journal of Research in Medical Sciences, 2017)
Background: This study evaluated the effects of adding Fentanyl 12.5 mcg to hyperbaric Bupivacaine 0.5% for spinal anesthesia with regards to the onset of sensory block, maximum sensory level reached and the time to achieve it, time to two dermatome segment regression, onset of motor block, time for maximum motor blockade, duration of motor block, hemodynamic parameters and incidence of side effects. Methods: Sixty patients, male and female, ASA I or ASA II, aged 18 to 65 years scheduled for elective lower abdominal and lower extremity surgeries were randomized into two groups. Group C (Control group) received 0.5% hyperbaric bupivacaine 13 mg (2.6 ml) and Group S (Study group) received 0.5% hyperbaric bupivacaine 13 mg (2.6 ml) and 12.5 mcg of fentanyl (0.25 ml). Intraoperatively, sensory parameters were assessed by pin-prick method and motor parameters were assessed by modified Bromage scale at different time intervals. Haemodynamic parameters were monitored and side effects were also observed. Results: Both groups were comparable with respect to age, height, weight and duration of surgery. There was statistically significant difference with regard to the onset of sensory block, maximum dermatome level, time to achieve it and time to two segment regression between the two groups. Motor parameters did not differ. Conclusions: It was concluded that the addition of 12.5 mcg Fentanyl to 13 mg of hyperbaric Bupivacaine 0.5% for spinal anesthesia significantly decreases the onset of sensory block, enhances the maximum dermatome level and also prolongs the time to segment regression with better hemodynamic stability.